2018
DOI: 10.1038/s41419-018-0839-8
|View full text |Cite
|
Sign up to set email alerts
|

MiR-361-3p regulates ERK1/2-induced EMT via DUSP2 mRNA degradation in pancreatic ductal adenocarcinoma

Abstract: Metastasis remains one of the most intractable challenges in pancreatic ductal adenocarcinoma (PDAC) biology, and epithelial-to-mesenchymal transition (EMT) is essential to the epithelium-originated solid tumor metastasis cascade. Emerging evidence demonstrates that aberrant miRNA expression is involved in pancreatic cancer progression. We found that miR-361-3p was associated with an advanced stage of PDAC and poor prognosis. Hence, the effect of miR-361-3p on metastasis of PDAC cells was evaluated using Trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 50 publications
5
62
0
Order By: Relevance
“…miRNAs act as oncogenes or tumor suppressors in tumors dependent on special conditions. miR-361-3p has been reported upregulated in various human tumors, including breast cancer, oral squamous cancer and pancreatic cancer (16,17,27). However, miR-361-3p functions in liver T-ICs have never been investigated before.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNAs act as oncogenes or tumor suppressors in tumors dependent on special conditions. miR-361-3p has been reported upregulated in various human tumors, including breast cancer, oral squamous cancer and pancreatic cancer (16,17,27). However, miR-361-3p functions in liver T-ICs have never been investigated before.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that miR-361-3p promotes human breast cancer cell viability by inhibiting the E2F1/P73 signaling pathway (16). Moreover, miR-361-3p regulates ERK1/2-induced EMT via DUSP2 mRNA degradation in pancreatic ductal adenocarcinoma (17). However, the function of miR-361-3p in liver T-ICs is unclear.…”
Section: Introductionmentioning
confidence: 97%
“…It is a prognostic biomarker in cutaneous leishmaniasis caused by L. braziliensis (Lago et al, 2018). Its expression was associated with better survival outcomes in cervical cancer (Hu et al, 2018). It also functions as an oncomiR in pancreatic ductal adenocarcinoma (Hu et al, 2018) and acts as a novel tumor suppressor for non-small cell lung cancer (Chen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of miR-206 increased the level of brain-derived neurotrophic factor (BDNF) improved memory of AD mice (Lee et al, 2012). Particularly, miR-361-3p, an important miRNA in the regulation of non-small cell lung cancer (Chen et al, 2016), pancreatic ductal adenocarcinoma (Hu et al, 2018), cervical cancer (Hu et al, 2018) and cutaneous leishmaniasis lesions (Lago et al, 2018), have been reported to be downregulated in AD (Wang et al, 2011). However, the pathological effect of miR-361-3p in AD and the possible molecular mechanisms are still poorly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Western blot analysis was performed as previously described. 20,23,24 Whole-cell lysates with approximately 30 μg of proteins were resolved on 10% or 12% SDS-PAGE and were subjected to western blot assay using the antibodies listed in Supplementary Materials. After appropriate secondary antibody incubation, the bands were visualized with the Molecular Imager System (BIO-RAD, Hercules, USA) using an enhanced chemiluminescence method (Thermo Fisher Scientific, USA).…”
Section: Western Blot Analysismentioning
confidence: 99%